2009
DOI: 10.1002/mc.20529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet B radiation on activator protein 1 constituent proteins and modulation by dietary energy restriction in SKH‐1 mouse skin

Abstract: The study examined the timing of modulation of activator protein 1(AP-1):DNA binding and production of AP-1 constituent proteins by ultraviolet B (UVB) radiation and effect of dietary energy restriction [DER, 40% calorie reduction from fat and carbohydrate compared to control ad-libitum (AL) diet] in SKH-1 mouse epidermis. AP-1:DNA binding by electromobility shift assay (EMSA) was increased in a biphasic manner after treatment with a tumor promoting suberythemal dose (750mJ/cm 2 ) of UVB light (311-313nm) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…A recent study demonstrated that 311-313 nm UVB radiation (dose: 750 mJ/cm 2 ) induced AP-1 binding to DNA [42]. These findings suggest that NB-UVB has the potential to modulate the expression of NGF in keratinocytes.…”
Section: Discussionmentioning
confidence: 92%
“…A recent study demonstrated that 311-313 nm UVB radiation (dose: 750 mJ/cm 2 ) induced AP-1 binding to DNA [42]. These findings suggest that NB-UVB has the potential to modulate the expression of NGF in keratinocytes.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, a number of changes similar to those seen in our current study have been observed in skin/epidermis of obese mice (either diet-induced or genetically-induced obesity) following exposure to UVB. In a study by Hopper et al (51), CR was reported to inhibit UVB-induced upregulation of AP-1:DNA binding and UVB-induced alteration in AP-1 constituent protein levels suggesting that CR inhibited events associated with UVB-mediated skin tumor promotion. Only limited information is available on the potential link between dietary energy balance and non-melanoma skin cancer (NMSC) in humans (reviewed in 52), however, stronger evidence points to a relationship between obesity and melanoma skin cancer (reviewed in 52).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that dietary energy restriction can reduce the incidence of both inherited and acquired cancers in experimental animals [256,258,[306][307][308][309]. Evidence also indicates that dietary energy restriction can reduce the incidence of several human cancers [310,311].…”
Section: Implications Of the Hypothesis To Cancer Preventionmentioning
confidence: 99%